C21 ACTIVE STAND TEST IN ALTERNATIVE TO HEAD UP TILT TEST AS NEUROMEDIATE SYNCOPE'S PREDICTOR IN COVID–19 PANDEMIC'S ERA: EXPERIENCE OF SINGLE CENTER. (18th May 2022) - Dentico, A; Ferrieri, A; Epicoco, G; Troccoli, R; Carretta, F; D'Agostino, C; Carretta, D
Abstract: Introduction: The Head Up Tilt Test is an exam that, with prolonged orthostatic stress, allows you to diagnose neuromediated syncope, but has the drawback of being a test that requires time, space and dedicated equipment. During the Covid pandemic, our Syncope Unit was limited both in terms of space and access. Not being able to perform the HUTT, it was decided to replace it with the Active Stand Test, a test that allows you to evaluate changes in blood pressure and ECG in a few minutes. The purpose of this study is to evaluate the effectiveness of the Active Stand Test as an alternative to HUTT in situations where the latter cannot be performed. Material and Method: In the period 2020–2021, 53 patients were treated for syncope at our center. These patients underwent initial evaluation, Active Stand Test and carotid sinus massage. The Active Stand Test was positive in 8 patients. In order to have a long–distance follow–up, a remote–controlled loop recorder was implanted in all patients. Two categories of patients were thus identified: asymptomatic patients for syncope, in whom no relevant symptoms or arrhythmias were found, and symptomatic patients for syncope. The first were followed only with remote control and telephone follow–up, symptomatic patients were reconvened for clinical re–evaluation. Results: Of the total 53 patients, 34 were asymptomatic patients with syncope and with no significant arrhythmia recordings and 19 were symptomatic patients with syncope. Of these, 5 were symptomatic for paroxysmal AVB and were implanted with PM, 1 for NSVT was protected with Life Vest; the 13 symptomatic without AVB (syncope of unknown origin) continued the follow–up. Among the latter we find the 8 patients who tested positive when performing the Active Stand Test carried out upon enrollment. The 34 patients asymptomatic for syncope were subsequently recalled to perform a HUTT. Conclusions: The emergence of the Covid–19 pandemic has led to a greater enhancement of the function of the Syncope Unit, making it the place of choice for the etiological diagnosis of syncope. This allowed for an important selection of the tests necessary to arrive at an etiological diagnosis of syncope. In a situation where the execution of the HUTT is difficult, the Active Stand Test made it possible to manage patients for the diagnosis of neuromediated syncopes.